Parametric design of daylight redirecting devices for dome buildings: case study of mosque buildings in Saudi Arabia - Alkhater, Mohammed (2024)
The presence of natural lighting in buildings enhances the visual appeal of internal areas and acts as a crucial connection between the inside and outside surroundings. Furthermore, the effective use of natural light can have a positive impact on the user's psychological well-being and provide substantial economic benefits by reducing energy consumption. However, daylight may be ineffective in deep, enclosed spaces within buildings. When there aren't enough light-control devices to enhance the amount of penetrating light on the windows, the problem becomes much worse. Mosques are one of the most obvious examples of this lighting problem. Therefore, in such architectural spaces, skylights or clerestory windows must be constructed under the dome ceiling to provide sufficient natural light in the middle zone. However, maintaining the required daylight coverage throughout the day in these areas remains a challenge. Consequently, the integration of advanced daylighting systems with dome geometry combined with parametric control and design could significantly enhance daylighting performance. This PhD thesis presents a new simplified control approach for automated louvres and an innovative method for designing passive daylight louvre systems integrated with dome parameters to optimise daylight utilization. The proposed control and design strategies aim to protect worshippers from direct sunlight and redirect it upwards on the dome surface, effectively distributing the redirected light across the prayer area using algorithmic methods. The reflective slats in the automated system have an individual and specific rotation angle to redirect sunlight to a fixed target over the dome ceiling, responding to the sun's movement parametrically. As for the compound parabolic reflector (CPR) louvre system, it collects and redirects sunlight within a defined angular range as a fixed daylighting system. Therefore, this process can simultaneously provide shading and optimise daylight usage. The impact of these daylight redirecting systems components has been discussed by integrating them with dome parameters, evaluating the redirect performance, and distributing daylight deep into the prayer hall. This study focused on enhancing daylight performance through the innovative use of reflector louvre daylighting systems, which attach to the windows in the drum with various orientations under the mosque's dome. The performance of the systems is incrementally developed using parametric modelling and gradually established to ensure the workflow's reliability. Using the Grasshopper plugin in Rhinoceros 3D, the geometric design and parametric control of rotation slats were performed. Meanwhile, Radiance and EnergyPlus in Grasshopper were utilised to evaluate the daylighting performance of shading systems, run via “Honeybee and Ladybug” environmental software plugins for Grasshopper. The evaluation process utilised advanced dynamic metrics, such as daylight glare probability (DGP), daylight distribution levels, and useful daylight illumination (UDI). The objective was to achieve a satisfactory daylighting quality that met the required illuminance levels for reading and praying, typically ranging between 150 ~ 500 lux for optimal visual comfort for the worshippers. The simulation studies were conducted at a typical mosque in Dhahran City, Saudi Arabia, during the noon prayer time. The results indicated that the automated parametric system improved the distribution of daylight within the prayer hall, with an average of 87% area coverage for the daylight illuminance range of 150–500 lx during the noon prayer period. This is about 21% to 48% higher than conventional blinds and clear-glazed windows, respectively. Moreover, the study revealed that the average amount of useful daylight entering the prayer hall can be significantly influenced by the shapes and tilts of the compound parabolic reflector (CPR) louvre system's parameters. The optimised reflector louvre system efficiently protects worshippers from direct sunlight and minimises potential glare, ensuring a favourable lighting environment during most prayer periods, by achieving values between 78% and 87% within the illuminance standard range of 150–500 lux.